PENGEMBANGAN MODUL KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) BERBASIS PROBLEM SOLVING UNTUK PESERTA DIDIK DI KELAS XI SMA/MA KURIKULUM 2013 - Novia Pradaristi; Erviyenni Erviyenni; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to develop Solubility and Solubility Constant Product (Ksp) module based on problem solving for Senior High School Students in 11th Grade Curriculum 2013 which is valid and practical. This type of research is research and development (R&D) which covering Define, Design, Develop, and Disseminate. The object of this research is module based on problem solving. The data collection instrument used are a validation sheet that given to three expert validators and user response questionnaire that given to three chemistry teachers and 20 Senior High School Students. Data analysis technique is by calculating the percentage score of validation and user response. The average score of the assessment by the validator team, i.e. self-instructional, self-contained, stand alone, adaptive, user friendly, IDEAL Problem Solving, pedagogic, and gradability aspects are 95,83%, 95,83%, 87,5%, 95,83%, 95%, 98,33%, 93,33%, dan 96,43%. Thus, the mean overall score of the solubility and Ksp module based on problem solving is 94,762% with ‘Valid’ category. The teacher’s average response to the module score os 91,667% with the croteria can be used without revision. The percentage of average score of student’s responses to developed module is 94% with the croteria can be used well. Based on the data analysis, it can be concluded that the module based on problem solving is valid and can be used well on subject of solubility and Ksp.Key Word : Module, Problem Solving, Solubility and Solubility Constant Product (Ksp).